2014
DOI: 10.1097/ftd.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic/Pharmacodynamic Model of Clozapine for Characterizing the Relationship Between Accumulated Exposure and PANSS Scores in Patients With Schizophrenia

Abstract: The PK/PD model can describe the clinical response as measured by decreasing PANSS score during treatment and may be useful for optimizing the dose regimen for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…e number of concentration readings (observations) ranged from 22 to 1617, with a median of 410, and the median observation per patient was 3. e daily dose was reported in nine studies with a median of 291 mg/day (134-540 mg/day) [15-19, 21, 22, 25, 26]. Most of the included studies used NONMEM software for population pharmacokinetic model [18,[20][21][22][23][24][25][26].…”
Section: Analysis Methods Used In Pharmacokinetics Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…e number of concentration readings (observations) ranged from 22 to 1617, with a median of 410, and the median observation per patient was 3. e daily dose was reported in nine studies with a median of 291 mg/day (134-540 mg/day) [15-19, 21, 22, 25, 26]. Most of the included studies used NONMEM software for population pharmacokinetic model [18,[20][21][22][23][24][25][26].…”
Section: Analysis Methods Used In Pharmacokinetics Modelmentioning
confidence: 99%
“…After abstract and title scanning, 15 articles were retained for final evaluation. A total of 12 studies [15][16][17][18][19][20][21][22][23][24][25][26] published between 1987 and 2019 were included in this review, as demonstrated in Figure 1. Study characteristics of the included publications, samples, and concentrations are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling and study simulation have been used to characterize the association between drug exposure and efficacy in studies of antipsychotic therapy for schizophrenia. 15,[17][18][19][20] The goal of the present analysis was to characterize the dose-response profile of lurasidone in the treatment of patients with bipolar depression to inform clinical dosing decisions and identify patient subgroups that might benefit from dose adjustments. Using data from registration studies of lurasidone in patients with bipolar depression, a population exposure-response model was developed to characterize Montgomery-Åsberg Depression Rating Scale (MADRS) 21 score change over time as a function of lurasidone dose.…”
Section: Introductionmentioning
confidence: 99%